Facile synthesis of lactoferrin conjugated ultra small large pore silica nanoparticles for the treatment of glioblastoma. Issue 40 (17th September 2021) - Janjua, Taskeen Iqbal; Ahmed-Cox, Aria; Meka, Anand Kumar; Mansfeld, Friederike M.; Forgham, Helen; Ignacio, Rosa Mistica C.; Cao, Yuxue; McCarroll, Joshua A.; Mazzieri, Roberta; Kavallaris, Maria; Popat, Amirali
Abstract : In this work, we successfully synthesise novel ultra-small (30 nm), large pore (7 nm) silica nanoparticles conjugated with lactoferrin a targeting ligand and demonstrate its utility for improving drug delivery across brain to treat Glioblastoma. Abstract : The blood brain barrier (BBB) and blood tumour barrier (BTB) remain a major roadblock for delivering therapies to treat brain cancer. Amongst brain cancers, glioblastoma (GBM) is notoriously difficult to treat due to the challenge of delivering chemotherapeutic drugs across the BBB and into the tumour microenvironment. Consequently, GBM has high rates of tumour recurrence. Currently, limited numbers of chemotherapies are available that can cross the BBB to treat GBM. Nanomedicine is an attractive solution for treating GBM as it can augment drug penetration across the BBB and into the heterogeneous tumour site. However, very few nanomedicines exist that can easily overcome both the BBB and BTB owing to difficulty in synthesizing nanoparticles that meet the small size and surface functionality restrictions. In this study, we have developed for the first-time, a room temperature protocol to synthesise ultra-small size with large pore silica nanoparticles (USLP, size ∼30 nm, pore size >7 nm) with the ability to load high concentrations of chemotherapeutic drugs and conjugate a targeting moiety to their surface. The nanoparticles were conjugated with lactoferrin (>80 kDa), whose receptors are overexpressed by both the BBB and GBM, to achieve additional active targeting. Lactoferrin conjugated USLP (USLP-Lf) were loaded with doxorubicin – a chemotherapy agent that is known to be highly effective against GBM in vitro but cannot permeate the BBB. USLP-Lf were able to selectively permeate the BBB in vitro, and were effectively taken up by glioblastoma U87 cells. When compared to the uncoated USLP-NPs, the coating with lactoferrin significantly improved penetration of USLP into U87 tumour spheroids (after 12 hours at 100 μm distance, RFU value 19.58 vs. 49.16 respectively). Moreover, this USLP-Lf based delivery platform improved the efficacy of doxorubicin-mediated apoptosis of GBM cells in both 2D and 3D models. Collectively, our new nano-platform has the potential to overcome both the BBB and BTB to treat GBM more effectively.